2013
DOI: 10.4028/www.scientific.net/amr.807-809.1031
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Persistence of Carbofuran in Peanut and Soil in Field Trails as Determined by GC-MS

Abstract: This paper investigated the analytical method of degradation and persistence of carbofuran, its metabolite 3-hydroxy carbofuran in peanut seeds, fronds and soils in field trial using gas chromatography mass spectrometry (GC-MS). Carbofuran 3GR formulation (3g a.i./100g) was applied at dosages of 2250 and 3375g ha-1in furrow at sowing peanut seeds in the fields of Langfang, Hebei province and Jinan, Shandong province, China, respectively. The soil and the plant samples were collected at different intervals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…carbofuran 3-OH was observed upto 1 day after application. Other scientists were also observed that 3-hydroxy carbofuran dissipated rapidly in soils it was not detect 7 days after application [19]. The residues of carbofuran and total carbofuran lost but at considerably slower pace in the latter phase of this study.…”
Section: Persistence and Dissipationmentioning
confidence: 39%
“…carbofuran 3-OH was observed upto 1 day after application. Other scientists were also observed that 3-hydroxy carbofuran dissipated rapidly in soils it was not detect 7 days after application [19]. The residues of carbofuran and total carbofuran lost but at considerably slower pace in the latter phase of this study.…”
Section: Persistence and Dissipationmentioning
confidence: 39%
“…It can also shorten the crop growth period and increase crop yields. CBF can be detected by mass spectrometry [1], chromatography [2][3][4][5], gas chromatography-mass spectrometry [6,7], enzyme inhibition method [8,9], and sensor or biosensor [10][11][12][13]. However, these operations are usually time-consuming and require expensive instruments, with complicated process of sample pretreatment.…”
Section: Introductionmentioning
confidence: 99%